Promoting Italian regional tourism in the 1930s: a qualitative analysis of English-language brochures and booklets for international visitors (Altre Modernità, 2025)
The aim of this work is to carry out a qualitative analysis of some English-language print material – mainly brochures and booklets – promoting Italian regional tourism during the 1930s. With the centralisation of the tourism industry under the Fascist regime in the 1930s (Berrino), Italy’s promotion as a tourist destination became primarily an economic and profitable opportunity (Syrjämaa Visitez). The analysis explores the “intersemiotic relations” (Barthes) between language and visual elements (photographs and other images such as drawings, maps, and so on) considered as a main strategy of cultural adaptation for international tourists. Using multimodal discourse analysis, particularly the theoretical model defined by Kress & van Leeuwen and Kress & Jewitt, the study examines how linguistic, visual, and cultural elements contributed to a “postcard effect” – a standardised representation of Italian regions within the English-speaking world and beyond – that shapes and reinforces the image of Italy as “Bel Paese” (Dann).
Keywords: Italian regional tourism; English-language brochures and booklets for international visitors; postcard effect; Bel Paese; multimodal discourse analysis; intersemiotic relations